Ergonomics Analysis for Subjective and Objective Fatigue Between Laparoscopic and Robotic Surgical Skills Practice Among Surgeons. (February 2020) - Rodrigues Armijo, Priscila; Huang, Chun-Kai; Carlson, Tyson; Oleynikov, Dmitry; Siu, Ka-Chun
Introduction . Our aim was to determine how self-reported and objectively measured fatigue of upper limb differ between laparoscopic and robotic surgical training environments. Methods . Surgeons at the 2016 SAGES Conference Learning Center and at our institution were enrolled. Two standardized surgical tasks (peg transfer [PT] and needle passing [NP]) were performed twice in each surgical skills practical environments: (1) laparoscopic training-box environment (Fundamentals of Laparoscopic Surgery [FLS]) and (2) Mimic dV-trainer (MIMIC). Muscle activation of upper trapezius (UT), anterior deltoid (AD), flexor carpi radialis, and extensor digitorum were recorded using surface electromyography (EMG; Trigno, Delsys, Inc, Natick, MA). Subjective fatigue was self-reported using Piper Fatigue Scale-12. Analysis was done using SPSS v25.0, α = .05. Results . Demographics were similar between FLS (N = 14) and MIMIC (N = 12). For PT, MIMIC had a significant increase in EMGRMS of UT ( P < .001) and AD ( P < .001). Conversely, FLS led to significant decreased muscle fatigue in UT ( P = .015). For NP, MIMIC had a significant increase in EMGRMS for UT ( P = .034) and AD ( P = .031), but FLS induced more muscle fatigue for AD ( P = .004). There was significant decrease in self-reported fatigue after performing FLS tasks ( P = .030) but not after MIMIC ( P = .663). Conclusion . Our results showed that practice with MIMIC resulted in greater activation of shoulder muscles, while FLS caused more significant muscle fatigue in the same muscles. This could be due to ergonomic disadvantages and nonoptimal ergonomic settings. Further studies are needed to understand the optimal ergonomics and its impact on fatigue and muscle activation during use of both the FLS and MIMIC training systems.